Cost-effectiveness of procalcitonin for detection of serious bacterial infections in children presenting with fever without source - Jefferson Antonio Buendía; Diana Guerrero Patiño (BMC, 2022)
Abstract Introduction Procalcitonin (PCT) offers better specificity than C-reactive protein (CRP) to detect SBI. However, their cost limited their use and routine application. The objective of this work is to determine the cost-effectiveness of PCT against CPR or Rochester scale in infants between 1 and 3 months from the perspective of the third payer in Colombia. Methods A Monte Carlo simulation was performed with a hypothetical cohort of 10,000 patients with fever without focus (FWS) between 1 to 3 months, to estimate the number of cases correctly diagnosed for each test and the associated costs with each test. Results The test with the highest number of correctly diagnosed cases was PCT 79%, followed by C-reactive protein 75%, and the Rochester scale 68%. The test with the lowest cost per patient was PCT $645 (95% CI US$646-US$645) followed by C-reactive protein U$ 653 (95% CI US$655-$645) and Rochester scale US$804 (95% CI US$807-US$804). This position of dominance of PCT eliminated the need to calculate an incremental cost effectiveness ratio. Conclusions PCT is the most cost-effective strategy for the detection of IBS in infants with FWS. These results should be interpreted within the clinical context of the patient and not as a single method for therapeutic decision-making.